2015
DOI: 10.1093/jxb/erv006
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping pipeline reveals major seedling root growth QTL in hexaploid wheat

Abstract: HighlightA phenotyping pipeline was used to quantify seedling root architectural traits in a wheat double haploid mapping population. QTL analyses revealed a potential major effect gene regulating seedling root vigour/growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
232
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(242 citation statements)
references
References 28 publications
9
232
0
1
Order By: Relevance
“…Hydroponic systems were reported to be handy tools for root phenotyping (Atkinson et al, 2015;Ayalew et al, 2015). The present study employed hydroponic culture to get easy access to intact roots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroponic systems were reported to be handy tools for root phenotyping (Atkinson et al, 2015;Ayalew et al, 2015). The present study employed hydroponic culture to get easy access to intact roots.…”
Section: Discussionmentioning
confidence: 99%
“…Sarker et al (2005) have reported in lentil that long root and shoot lengths at seedling stage were highly correlated with high grain yield. Initial root parameters and above-ground biomass were also reported to be positively correlated in wheat (Atkinson et al, 2015). Among the seedling traits that enable plants withstand drought are early establishment and ground cover, deep root system and leaf waxiness (Blum, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the process of automatically acquiring images of plants and their subsequent analysis is complex, and requires an understanding of the software processes at work, and their limitations (Pridmore et al 2012). The combination of rapid image capture and high throughput, objective analysis, though, has been shown to lead to new genetic insight (Atkinson et al 2015). These potential rewards then, and the necessity for specialist knowledge to apply and develop the underlying systems, provide the motivation for the timely application and development of image analysis to plant biology.…”
Section: Introductionmentioning
confidence: 99%
“…Most root phenotyping platforms focus on measurements at high throughput of selected root traits on a large number of plants, with the objective of detecting quantitative trait loci usable in breeding (Kuijken et al, 2015). For example, Atkinson et al (2015) reported a phenotyping platform where root systems grow in 2D on a filter paper for a few days. Platforms where root systems grow in 3D also have been developed (IyerPascuzzi et al, 2010) and used for quantitative trait locus detection (Topp et al, 2013).…”
mentioning
confidence: 99%